(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Reseach target the most important topic, is Activity and ProfitabilityIndictors Analysis for Nationality and Iraqi Insurance Company, In order to stand on them ability to cover its risks and explore the efficiency asset and its avialible resources using to determine them abilities to profit generation from its insurance activity. The analysis was focus to examine their profit and activity power, and test the significant differences aming them performance. Test 2 hypothese that is related and result it sign that the 2 company no has significant differences at profitability and activity level. The research depend on coneclusion, recommended two company to work at efficiency with cost element of insurance activity in order to maximize the insurance surpluse average, by using the successful viechals to insurance services marketing to large number of insurance applicatoers according to apply the electronic management requirement